O uso do tempo de idosos que participam de grupos para terceira idade do município de São Carlos - Paganelli, Luiza Oliva (2015)
Time is a key resource for humans, structuring its activities and daily life. This daily life organization also develops itself based on interests, wills, social roles and life stages of the subject. Regarding the elderly, studies show there specific occupations to this life stage, due to the transition of productive life for retirement. Whereas inherent specificities of this phase, this work aims to investigate the use of time for the elderly, identifying the complexity and the diversity of activities of this population. It were identified the social and physical context of these activities as well significance and satisfaction levels that the elderly attribute to the activities when performed. The sample consists of 51 elderly from São Carlos who participated in two seniors programs. It were as collection instruments The Daily Activities and semistructured interviews. The results showed that most of their time was spent with Activities of Daily Life and Practical Life (70%), followed by Leisure Activities (24%) and other (6%). According to the physical context, the home itself is where the participants performed the activities. Most of the time the elderly was alone (13.6 hours), but when accompanied, their main companies were family members (spouses and children). The sample was divided into groups, in order to accomplish comparisons in patterns of time use and their determinants among the groups. In general, it was found that there were no significant differences between the groups regarding the time use and physical contexts in which the activities were developed. As for the social context, it were found significant differences, being the elderly aged less or equal to 69 years (p=0,012) and those who were married (p=0,000) performed their activities more time together than alone. It was found that the day was almost fully occupied with satisfactory and meaningful activities for the sample, even if the elderly who practiced exercises have shown higher rates of satisfaction (p=0,045). This study may portray the time use of a portion of elderly, as well as their interests, preferences and needs. Thus, we can shed light to the knowledge of Occupational Therapy and many other areas that focus on the elderly population.